ANATOMY OF A LIE: MAPPING THE STRUCTURE AND SPREAD OF HOAXES IN THE DIGITAL AGE - Erik Saut Hatoguan Hutahaean; Al-Amin (Adisam Publisher, 2025)
In the digital era, the spread of hoaxes or fake news has become an increasingly complex and worrying phenomenon. Hoaxes are not just misinformation, but have a systematic structure and pattern of dissemination, fuelled by political and economic gain, or simply provocation. Social media and digital platforms play a major role as catalysts for the spread of hoaxes due to their characteristics of wide reach, speed of dissemination, and low filtering of truthful information. Mechanisms such as echo chambers and digital platform algorithms amplify the effects of hoaxes, increasing the risk for individuals with low digital literacy. To counter the negative impact of hoaxes, strategic measures are needed such as improving digital literacy, strengthening education on information verification, and developing effective regulations in the digital world. Collaboration between the government, digital platforms and the public is essential to address the threat posed by hoaxes, as well as to shape a more critical and informed society.